University Education, Public Research and Employment Growth in Regions - An Empirical Study of Germany - Thomas Brenner; Charlotte Schlump (Philipps-University Marburg, Department of Geography, 2010)
Universities and research institutes are seen as important drivers of the regional economy. Their impact on regional entrepreneurial and innovation activity is well documented. On the other hand, their influence on regional employment growth is less researched. This paper provides an extensive empirical analysis of the relationship between the education of university graduates and employees in research institutes and the growth of employment in a region. The analysis is done for nine industries separately. We find that university graduates have a significant influence on employment growth in several industries, while an influence of public research institutes is found only for a few industries. For most control variables the findings differ between manufacturing and service industries. Such a clear difference between the two types of industries is not found for university graduates and public research institutes.
Keywords: H52; I2; J20; 330; Universities; Research Institutes; Regional Employment Growth